KARAKTERISTIK TOKOH UTAMA PADA CERPEN URBANDIT KARYA DJENAR MAESA AYU SERTA APLIKASINYA DALAM PEMBELAJARAN BAHASA DAN SASTRA INDONESIA - Rerin Maulinda (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2018)
Short stories provide space for readers to see human life and humanity. Things related to marriage, romance, tradition, religion, friendship, social, political, educational and others. In this analysis the use of the descriptive method of analysis provides proof of the character possessed by the five figures in Urbandit's story. Nayla is a mother of a daughter who lives together as a novelist. Ara is a woman who chooses life to satisfy her desires. Yana is a good friend but her husband disappoints only because of a shortage in her that creates an affair on the part of her husband. Where this makes Yana change herself with plastic surgery. Lila is a beautiful woman who has chosen to support herself by entering the world of Pimps. And the last is Anya who feels unhappy just because of her biological dissatisfaction with her husband. So looking for the wrong party at the night club. However, this difference did not make them far apart and remained in their friendship relationship until now.